Systematic Affinity Purification Coupled to Mass Spectrometry Identified p62 as Part of the Cannabinoid Receptor CB2 Interactome - Sharaf, Ahmed; Mensching, Leonore; Keller, Christina; Rading, Sebastian; Scheffold, Marina; Palkowitsch, Lysann; Djogo, Nevena; Rezgaoui, Meriem; Kestler, Hans A.; Moepps, Barbara; Failla, Antonio Virgilio; Karsak, Meliha (Frontiers in Molecular Neuroscience, 2019)
The endocannabinoid system (ECS) consists particularly of cannabinoid receptors 1 and 2 (CB1 and CB2), their endogenous ligands, and enzymes that synthesize and degrade their ligands. It acts in a variety of organs and disease states ranging from cancer progression over neuropathic pain to neurodegeneration. Protein components engaged in the signaling, trafficking, and homeostasis machinery of the G-protein coupled cannabinoid receptor 2, are however largely unknown. It is therefore important to identify further interaction partners to better understand CB2 receptor functions in physiology and pathophysiology. For this purpose, we used an affinity purification and mass spectrometry-based proteomics approach of Strep-HA-CB2 receptor in HEK293 cells. After subtraction of background interactions and protein frequency library assessment we could identify 83 proteins that were classified by the identification of minimally 2 unique peptides as highly probable interactors. A functional protein association network analysis obtained an interaction network with a significant enrichment of proteins functionally involved in protein metabolic process, in endoplasmic reticulum, response to stress but also in lipid metabolism and membrane organization. The network especially contains proteins involved in biosynthesis and trafficking like calnexin, Sec61A, tubulin chains TUBA1C and TUBB2B, TMED2 and TMED10. Six proteins that were only expressed in stable CB2 expressing cells were DHC24, DHRS7, GGT7, HECD3, KIAA2013, and PLS1. To exemplify the validity of our approach, we chose a candidate having a relatively low number of edges in the network to increase the likelihood of a direct protein interaction with CB2 and focused on the scaffold/phagosomal protein p62/SQSTM1. Indeed, we independently confirmed the interaction by co-immunoprecipitation and immunocytochemical colocalization studies. 3D reconstruction of confocal images furthermore showed CB2 localization in close proximity to p62 positive vesicles at the cell membrane. In summary, we provide a comprehensive repository of the CB2 interactome in HEK293 cells identified by a systematic unbiased approach, which can be used in future experiments to decipher the signaling and trafficking complex of this cannabinoid receptor. Future studies will have to analyze the exact mechanism of the p62-CB2 interaction as well as its putative role in disease pathophysiology.